AIR QUALITY MONITORING USING SENSING DEVICES IN URBAN CITY - T, Devi; Teja, R Ravi; G, Rahul; M, Rahul; K, Rajesh (The journal of contemporary issues in business and government, 2021)
Motivated by the expansion of air contamination, we watch the properties of air has procured consideration in theoretical investigation and practical execution. Here, we present the architecture, implement, improve the quality for air sensing system, which will be providing current and close-grain air attribute map of the observed area. The aim is to reduce the mean error of current- time air quality map established involving data assumption of the unmeasured values.